Regulating sex, work: from crime control to neo-liberalism? - Scoular, Jane (Wiley-Blackwell, 2010)
Introduction : the changing social and legal context of sexual commerce : why regulation matters / Jane Scoular and Teela Sanders -- What's law got to do with it? How and why law matters in the regulation of sex work / Jane Scoular -- Mainstreaming the sex industry : economic inclusion and social ambivalence / Barbara G. Brents and Teela Sanders -- The movement to criminalise sex work in the United States / Ronald Weitzer -- When (some) prostitution is legal : the impact of law reform on sex work in Australia / Barbara Sullivan -- Labours in vice or virtue? Neo-liberalism, sexual commerce, and the case of Indian bar dancing / Prabha Kotiswaran -- Male sex work : exploring regulation in England and Wales / Mary Whowell -- Bellwether citizens : the regulation of male clients of sex workers / Belinda Brooks-Gordon -- Extreme concern : regulating 'dangerous pictures' in the United Kingdom / Feona Attwood and Clarissa Smith -- Consuming sex : socio-legal shifts in the space and place of sex shops / Baptiste Coulmont and Phil Hubbard -- Cultural criminology and sex work : resisting regulation through radical democracy and participatory action research (PAR) / Maggie O'Neill